2022
DOI: 10.3390/molecules27165207
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer Effects of Auranofin in Human Lung Cancer Cells by Increasing Intracellular ROS Levels and Depleting GSH Levels

Abstract: Auranofin, as a thioredoxin reductase (TrxR) inhibitor, has promising anti-cancer activity in several cancer types. However, little is known about the inhibitory effect of auranofin on lung cancer cell growth. We, therefore, investigated the antigrowth effects of auranofin in various lung cancer cells with respect to cell death, reactive oxygen species (ROS), and glutathione (GSH) levels. Treatment with 0~5 µM auranofin decreased cell proliferation and induced cell death in Calu-6, A549, SK-LU-1, NCI-H460, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 73 publications
2
30
0
Order By: Relevance
“…Myosin (MYH-9), plectin (PLEC), talin (TLN1), and annexins are responsible for cell–cell and cell–protein interactions accompanied by kinase M3K5 make up the system responsible for cytoskeleton reorganization essential for the cell motility and the wound healing process [ 20 , 55 ]. The abundance of peptides representing those proteins significantly decreased due to the exposure of cells to auranofin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Myosin (MYH-9), plectin (PLEC), talin (TLN1), and annexins are responsible for cell–cell and cell–protein interactions accompanied by kinase M3K5 make up the system responsible for cytoskeleton reorganization essential for the cell motility and the wound healing process [ 20 , 55 ]. The abundance of peptides representing those proteins significantly decreased due to the exposure of cells to auranofin.…”
Section: Resultsmentioning
confidence: 99%
“…Both moieties of auranofin can inhibit thioredoxin reductase (TrxR) and glutathione peroxidase (GPx) [ 18 , 19 ]. As both proteins contain thiol and selenol groups, auranofin’s presence also significantly depletes the reduced form of glutathione [ 20 ]. All three biocompounds are responsible for ROS regulation, and their amounts tend to be significantly higher in cancer cells, especially in non-small cell lung carcinoma [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the nitrated [6,6,6]tricycle-derived compound SK1 triggered GSH depletion, leading to ROS overproduction in oral cancer cells [ 49 ]. Auranofin exhibits antiproliferation by ROS induction and GSH depletion in lung cancer cells [ 50 ]. Moreover, examining the status of antioxidant levels for 3HDT treatment is necessary because oxidative stress was upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer treatment targeting the developed antioxidant system in cancer cells is a promising and efficient approach ( Moloney & Cotter, 2018;Prasad et al, 2017). Auranofin exerts anticancer activity by inducing oxidative stress, which increases ROS generation through TrxR inhibition (Cui et al, 2022;Hwang-Bo et al, 2017). Spermidine, selected as the second drug in the combination therapy, is a polyamine abundant in seaweed and exerts various biological functions (Kumar et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Auranofin is a thioredoxin reductase (TrxR) inhibitor, which acts as a regulator of cellular redox, cell proliferation, and a component of antioxidant systems (Abdalbari & Telleria, 2021). Cui et al (2022) have demonstrated that auranofin can induce apoptosis in human lung cancer cells by increasing the accumulation of reactive oxygen species (ROS) via inhibition of TrxR activity and glutathione depletion. Furthermore, auranofin exerts anticancer activity by inactivating extracellular signal-regulating kinase and protein kinase B (Akt), accompanied by mitochondrial dysfunction through the modulation of B-cell lymphoma 2 (Bcl-2) family proteins (Wen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%